Mathematics Learning Revolution: Implementation of Geogebra in Spldv Material - Cartini, Nining; Cita Dwi Rosita; Setiyani, Setiyani (PT Inovasi Pratama Internasional, 2024)
This article discusses the use of GeoGebra as a tool in learning Systems of Linear Equations in Two Variables (SPLDV). GeoGebra, created by Markus Hohenwarter in 2001, has grown to become one of the most popular educational tools worldwide, allowing students and teachers to explore mathematical concepts visually and interactively. With features such as graph generation, mathematical object manipulation, and intersection analysis, GeoGebra facilitates a deeper understanding of SPLDV. The purpose of this article is to explain how using GeoGebra can simplify the learning process for Systems of Linear Equations in Two Variables (SPLDV). The research methodology used includes qualitative and quantitative approaches, by measuring student understanding before and after using GeoGebra. The research results show that GeoGebra not only improves understanding of mathematical concepts, but also develops students' problem solving and critical thinking skills. Thus, GeoGebra contributes significantly to improving the quality of mathematics teaching and learning.